2015
DOI: 10.1097/wno.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Oculomotor Nerve Paresis With Isolated Cyclic Pupillary Spasms

Abstract: Cyclic oculomotor nerve paresis is a rare and usually congenital disorder. It is characterized by unilateral third nerve paresis with periodic spasms causing eyelid elevation, miosis, and contraction of 1 or more of the extraocular muscles innervated by the third nerve. We report a 20-month-old girl who presented initially with a congenital partial right third nerve paresis without ptosis. She subsequently developed isolated cyclic spasms of the pupil followed several months later by permanent partial ptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Levator shortening and lid suspension can assist with the ptosis but must be carefully weighed with the risk of corneal exposure [1,4]. Currently, no treatment has been proven to have an effect on cyclic spasms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Levator shortening and lid suspension can assist with the ptosis but must be carefully weighed with the risk of corneal exposure [1,4]. Currently, no treatment has been proven to have an effect on cyclic spasms [5].…”
Section: Discussionmentioning
confidence: 99%
“…The history and examination findings in Case 4 helped make the diagnosis of oculomotor nerve paresis with cyclic spasm, which is a rare congenital condition that is usually not associated with tumors, except in rare cases of a glioma (16). Therefore, neuroimaging studies are usually normal.…”
Section: Case 5: Radiation-induced Cn III Palsy With Neuromyotoniamentioning
confidence: 99%
“…During the spastic phase, the pupil undergoes miosis, lid elevation, and esotropia, whereas during paralysis, the pupil undergoes mydriasis, ptosis, and exotropia. Isolated cyclic pupillary spasms have only been reported by Salman et al (3) in a child with congenital oculomotor nerve paresis. In this article, we report the case of an adult presenting with oculomotor nerve paresis with mainly pupillary cyclic spasms without any changes in the eyelid or cyclic eye movement.…”
mentioning
confidence: 93%
“…To the best of our knowledge, isolated cyclic pupillary spasms have previously been reported in only 1 case of an 18-month-old girl, in whom congenital oculomotor nerve paresis was diagnosed when she was age 4 months (3). Although our patient was an adult, a review of her family photograph album revealed ptosis in her right eye when she was age 3 years (see Supplemental Digital Content , Supplemental Material 2 , http://links.lww.com/WNO/A657).…”
mentioning
confidence: 94%